Platelets in Thrombo-Inflammation: Concepts, Mechanisms, and Therapeutic Strategies for Ischemic Stroke - Burkard, Philipp; Vögtle, Timo; Nieswandt, Bernhard (Hämostaseologie, 2020)
Platelets are anucleate cells known for their essential function in hemostasis and formation of thrombi under pathologic conditions. In recent years, strong evidence emerged demonstrating the critical involvement of platelets in inflammatory processes including acute ischemic stroke (AIS), which is one of the leading causes of death and disability worldwide. Recanalization of the occluded brain artery to reconstitute cerebral blood flow is the primary goal in the treatment of stroke patients. However, despite successful reperfusion many patients show progression of infarct sizes, a phenomenon referred to as ischemia/reperfusion injury (I/RI). Cerebral I/RI involves both thrombotic as well as inflammatory pathways acting in concert to cause tissue damage, defining AIS as a prototypic thrombo-inflammatory disease. Currently used antiplatelet drugs applied to AIS patients eventually increase the risk of partially life-threatening hemorrhages, making more targeted pharmacological intervention necessary. Experimental evidence indicates that inhibition of platelet surface receptors that regulate initial platelet adhesion and activation might be suitable targets in thrombo-inflammatory settings, while inhibitors of platelet aggregation are not. In this review, we will summarize the recent developments in elucidating the role of the main platelet receptors in AIS and discuss their potential as pharmaceutical targets. Furthermore, we will also briefly discuss the important platelet-triggered intrinsic coagulation pathway with the pro-inflammatory kallikrein–kinin system in the context of ischemic stroke.
Keywords: platelet; platelet receptors; stroke; thrombo-inflammation; FXII